ASSESSMENT OF FIXED ASSETS REPRODUCTION IN AGRICULTURE - Nikitin, Alexander; Larshina, Tatiana; Voropayeva, Victoria; Beketov, Andrey; Selyanko, Daria (Revista Inclusiones, 2020)
The article discusses the methodological aspects of assessing the effective reproduction of fixed assets. The authors have systematized and supplemented indicators characterizing the fixed assets reproduction. The quantitative and qualitative characteristic of the level of fixed assets reproduction using the proposed system of indicators allows giving a comparative quantitative assessment of the degree of correspondence of the means of production of agricultural enterprises to the level of development of scientific and technological progress, as well as carrying out an economic assessment of the directions of the fixed assets reproduction and assessing the degree of the impact of the level of fixed assets reproduction of agricultural enterprises on improving the efficiency of the regional market of material and technical resources. The technique has been tested on the example of agricultural enterprises in the Tambov region.